Management Of Majelis Taklim Darussunnah In Fostering Sakinah Family In Bilah Hulu Labuhanbatu District - Wiranda, Gusti Bayu; Soiman, Soiman (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
This research aims to describe the management functions applied by Majelis Taklim Darussunnah in fostering a sakinah family. Without the provision of religious knowledge, it is difficult for individuals to build a sakinah family. This study employs a stepwise method with a descriptive scheme. The sources of information include four informants from the management of Majelis Taklim Darussunnah. Data collection methods involve assessments, interviews, and document analysis. The study results indicate that the management functions applied by Majeli Taklim Darussunnah in fostering sakinah families include planning, organizing, implementation, supervision, and evaluation. These management functions can effectively be used to foster sakinah families.